SGLT-2 inhibitors: the glucosuric antidiabetics - Thaddanee, Rekha; Khilnani, Ajeet Kumar; Khilnani, Gurudas (International Journal of Basic & Clinical Pharmacology, 2017)
Despite availability of a number of oral antidiabetics, a sizeable population of diabetics remains uncontrolled. Thus there is growing need of new group of drugs for diabetic control. Understanding renal conservation of glucose by efficient reabsorption through sodium glucose cotransporter-2 (SGLT-2) has paved way for development of an entirely new group of drugs, the SGLT-2 inhibitors. These glucosuric antidiabetic agents have shown promise in early clinical studies. Canagliflozin is recently approved for use in diabetes alone or along with other antidiabetics. Other highly selective inhibitors undergoing various stages of clinical developments are dapagliflozin, sergliflozin, remogliflozin, ipragliflozin, empagliflozin, luseogliflozin, tofogliflozin and desoxyrhaponticin. KGA-2727 (pyrazole-O-glucoside) is the first selective SGLT-1 inhibitor undergoing intense preclinical testing. There are safety issues associated with this group like urogenital infections (fungal), weight loss, initial osmotic diuresis and increased incidence of cardiovascular events. The long term safety remains to be established. Despite these limitations, SGLT-2 inhibition offers a unique target for achieving adequate control of diabetes in adults.